Newly qualified midwives' perceptions of their level of midwifery clinical competence during community service in KwaZulu-Natal, South Africa - Amanda B. Ngcobo; Olivia B. Baloyi; Mary Ann Jarvis (AOSIS, 2021)
Background: There are links between the inadequate numbers of competent midwives and high maternal mortality ratios and neonatal mortality rates which highlights the significance of job-ready, newly qualified midwives who can display clinical competence. The South African Nursing Council regulated mandatory community service, as a supportive year to develop clinical competence. Aim: To explore and describe newly qualified midwives' perceived level of midwifery clinical competence during community service. Setting: Both the event of the pandemic and the distribution of the potential participants across various geographical settings necessitated planning for data collection in real and online settings convenient to them. Method: Non-probability purposive sampling was utilized to select and invite the post community service, newly qualified midwives (N = 65), of the select university, who underwent community service in 2018 and experienced exposure to maternity care settings in the eThekwini District (n = 23). Data were collected through five focus groups and analysed through Elo and Kyngas' content analysis. Results: Three categories emerged: transitioning from the sheltered education environment to the real practice world, support in practice: disparate realities and interception of mentorship. Six subcategories accompanied the categories. Conclusion: Newly qualified midwives' clinical confidence and competence transitioning from the safe academic environment to the authentic accountable clinical setting hinges on mentorship and welcoming, non-stigmatising supportive relationships that facilitate the integration of previous learnings into community service practice. Contribution: The study allows for audibility and awareness of the transitioning midwives' perceptions highlighting the significance to maternity staff and policy makers, of supportive relationships and structures.